Hematologic and biochemical reference intervals and blood cell morphology in South American pit vipers (Bothrops pubescens). (1st September 2021) - Bilhalva, Lina C.; Winter, Acácia B.; Oberrather, Karina; Toso, Marina R.; Oliveira, Thaiane A.; Almeida, Bruno A.; Soares, João Fabio; Valle, Stella F.
Abstract: Background: The maintenance of snakes in captivity for venom extraction and antivenom production is essential due to the high incidence of snake envenomation in Latin America and the Caribbean. Hematology and biochemistry are valuable in the laboratory evaluation of these animals, which indirectly improves their health and welfare. Objectives: The objective of this study was to determine the reference intervals for hematologic and plasma biochemistry variables in Bothrops pubescens snakes kept in captivity and to examine sex variation. Methods: Blood samples from 20 healthy B pubescens snakes were collected for hematologic and biochemistry evaluations and compared between sexes. The sample analysis consisted of a complete blood count using manual methods previously described, and blood cell morphology evaluation. Plasma biochemistry consisted of albumin, uric acid, aspartate aminotransferase, creatine kinase, and total plasma protein measurements. Results: Hematologic and biochemical variables were demonstrated to be different when compared with previously published values. A difference between the sexes was not observed for B pubescens . Conclusions: Given that many illnesses can lead to laboratory alterations, knowledge about the reference intervals of healthy captive animals is essential to evaluate the health status and correct management of these snakes.